DISINTEGRANTS AND THEIR INFLUENCE ON THE DISSOLUTION OF SUBSTANCES OF BIOPHARMACEUTICAL CLASSIFICATION SYSTEM CLASSES - I. E. Smekhova; V. A. Vainshtein; Y. M. Ladutko; O. V. Druzhininskaya; N. N. Tureckova (Разработка и регистрация лекарственных средств, 2019)
The characteristic of disintegrants used in technology of solid dosage forms is reviewed. The effect on release of substances of different classes from the tablets according to the biopharmaceutical classification system is presented. The characteristic of disintegrants used in technology of solid dosage forms is reviewed. The mechanisms of their action and methods of compounding into tablets, as well as factors that must be considered when choosing the optimal disintegrant, are given. The results of studies on the effectiveness of various disintegrants (crospovidone, croscarmellose sodium, sodium starch glycollate, etc.) on the release of active substances of different classes according to the biopharmaceutical classification system from tablets are discussed. A promising use of co-disintegrating agents in the technology of tablets of substances of class II BCS is highlighted. Examples of disintegrants of natural origin (mucus) used in tablets dispersed in the oral cavity are given.